Ajaran Budi Pekerti dalam Iluminasi Naskah Babad Kartasura - Sukawati - Venny Indria Ekowati; Sri Hertanti Wulan; Aran Handoko; Nur Hanifah Insani (Manuskripta, 2018)
This research aims to identify and anylize character building that include in the illumination the text of Babad Kartasura-Sokawati. The data collected through content anylisis and photography. Overall, illuminations picture that include in the text of Babad Kartasura-Sokawati contain character building of Javanese people. There are six character buildings that appear from the illumination, there are: 1) leadership value that appeared from the pictures of eagle, peacock, deer, kingdom’s flag, weapons, bridge fence, star, sun, mountain, river, forest, khandhil (oil lantern), leaf lined, lotus, and sunflower; 2) respect and honorable value that appeared from the pictures of eagle, peacock, kingdom’s flag, dhampar (the king’s seat), leaf lined, and sunflower; 3) value of the perfection of life that appeared from the pictures of khandhil (oil lantern), sunflower, and vines; 4) devotion value that appeared from the pictures of the star and the moon; 5) value to achieve peacefully of the inner and outer that appeared from the pictures of water waves; and 6) noble character value that appeared from the pictures of songsong (gold umbrella), leaf lined, rose, and sunflower. --- Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis ajaran budi pekerti di dalam iluminasi teks Babad Kartasura-Sokawati. Data dikumpulkan dengan analisis isi dan dokumentasi. Secara keseluruhan gambar iluminasi yang terdapat dalam teks Babad Kartasura-Sokawati memuat ajaran budi pekerti yang selaras dengan kehidupan masyarakat Jawa. Terdapat enam ajaran budi pekerti yang terdapat dalam gambar iluminasi, yaitu: 1) ajaran tentang kepemimpinan yang tersurat dari gambar burung garuda, burung merak, kijang, umbul-umbul, senjata, pagar jembatan, bintang, matahari, gunung, sungai, hutan, khandhil (lentera minyak), daun yang berjajar, bunga teratai, dan bunga matahari; 2) ajaran saling menghormati dan menghargai yang tersurat dari gambar burung garuda, burung merak, umbul-umbul, pagar jembatan, dhampar (kursi raja), daun yang berjajar, serta bunga mawar; 3) ajaran tentang kesempurnaan hidup yang tersurat dari gambar khandhil (lentera minyak), bunga matahari, dan tumbuhan sulur; 4) ajaran ketaqwaan yang terdapat dalam gambar bintang dan bulan sabit; 5) ajaran untuk meraih ketentraman lahir dan batin yang tampak pada gambar gelombang air; serta 6) ajaran berpekerti luhur yang tampak dari gambar songsong (payung emas), daun yang berjajar, bunga mawar, dan bunga matahari.